EXTH-25. DIANHYDROGALACTITOL (VAL-083) REDUCES GLIOBLASTOMA TUMOR GROWTH IN VIVO, UPON BEVACIZUMAB-INDUCED HYPOXIA. (5th November 2018) - Golebiewska, Anna; Oudin, Anais; Steino, Anne; Niclou, Simone; Brown, Dennis; Bacha, Jeffrey
Abstract: Standard-of-care for glioblastoma (GBM) includes surgery, radiation and temozolomide. Nearly all tumors recur and 5-year survival is less than 3%. Unmethylated promoter status for O 6 -methylguanine-DNA-methyltransferase (MGMT) is a validated biomarker for temozolomide-resistance. Second-line treatment with bevacizumab has not only failed to improve survival, but has also been shown to induce intratumor hypoxia, which is implicated in increased chemoresistance. VAL-083 is a bi-functional DNA-targeting agent that readily crosses the blood-brain barrier. VAL-083 targets N 7 -guanine, causing DNA double-strand breaks and cancer cell-death in GBM cancer stem cells (CSCs) and non-CSCs, independent of MGMT. We have previously shown that bevacizumab treatment upregulates expression of glucose transporters GLUT-1/GLUT-3 on GBM cells. We hypothesized that, based on its unique monosaccharide backbone structure, VAL-083 may benefit from bevacizumab-induced GLUT transporter upregulation leading to enhanced VAL-083 uptake and anti-tumor activity. Methods: To investigate the in vivo anti-tumor effect of VAL-083+bevacizumab, we used a orthotopic patient-derived xenograft GBM model. All mice carried MGMT -unmethylated, temozolomide-resistant recurrent T16 GBM tumors as detected by MRI 35 days post-implantation. Mice were grouped into control, bevacizumab, VAL-083, and VAL-083+bevacizmab. Tumor progression was measured by MRI on days 49 and 56, and tumor growth rate was calculated for the entire study (day 35 vs. 56) and for the last 7 days (day 49 vs. 56). Results: Tumors were significantly smaller in VAL-083-treated mice both compared to control (-83%, p<0.001) and compared to bevacizumab-treated (-75%, p<0.001) mice. Additionally, analysis of tumor growth in-time showed significantly reduced tumor growth rate for VAL-083+bevacizumab compared to VAL-083 alone (p<0.01). Conclusions: These results show strong in vivo anti-tumor efficacy of VAL-083 against MGMT -unmethylated, temozolomide-resistant recurrent GBM. This effect was further augmented in combination with bevacizumab, providing rationale of clinical investigation in combination with bevacizumab in the treatment of GBM.